Pengaruh Model Discovery Learning terhadap Kemampuan Pemahaman Matematis Peserta Didik SMP - aulia, kharisma; Sari, Indah Puspita (Universitas Muria Kudus, 2024)
Currently, the learning model used is still conventional which causes students to be less active in the learning process. The purpose of this study was to determine the effect of the Discovery Learning model on the mathematical understanding ability of junior high school students. The research method used is an experimental method using a posttest only control design. The population of the study was grade VIII students at SMP Negeri 2 Cimahi. The subjects in this study were students including class VIII-J as a control class using conventional learning 37 people and class VIII-F as an experimental class given treatment in the form of learning with the discovery learning model as many as 37 people. The data analysis technique used was to use the normality test, homogeneity test, and t-test, where the sig. (2-tailed) result was 0.002 smaller than 0.05. From this study it can be said that the mathematical understanding ability in the control and experimental classes is normally distributed and has a homogeneous variance. Then based on the results of the t-test H0 was rejected and H1 was accepted and a difference was found between the experimental and control classes. Therefore, the Discovery Learning learning model in the experimental class, namely in class VIII-F, can improve the mathematical understanding abilities of junior high school student.